(3EbJUGOjGJ fXe GdeYdheGJ GdeMGSHjI hGdEOGQjIs - (3UdGM GdOjf YHO GdefYe(B, (3eHGQcs ((3GdEScfOQjI(B:s (3OGQ GdLGeYI GdLOjOI ddfTQ(B,s, 2001)
(3OQGSI eaghe GdeYdheGJ hYdGbJg HfXGe GdeYdheGJ GdeMGSHj ddeTQhYGJ(B- (3feGPL GdJcdaI hGdefaYI dCfXeI GdeYdheGJ GdeMGSHjI(B- (3GdEWGQ GdTGed dJbjje CfXeI GdeYdheGJ GdeMGSHjI(B.s
Keywords: (3GdEOGQIs; (3GdeMGSHIs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s